Analisis Performa Routing SPIN (Sensor Protocol for Information Via Negotiation) pada Wireless Sensor Network - Salsabila Salsabila; Rakhmadhany Primananda; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network is a network consisting of several nodes that have dynamic properties. This technology can be used to solve existing problems on routing. An example is SPIN routing. In this research the writer tries to analyze SPIN-BC and SPIN-RL routing, which SPIN-BC and SPIN-RL routing can overcome traffic queue on data delivery and can communicate more than one node (broadcast). The research aimed at determining the performance of SPIN-BC and SPIN-RL. routing anymore and the performance of both routing that were done by testing with some parameters. These parameters were Average Latency, Number Data Packets Forwarded, Tx Power, Number Tx.Frames and Memory Node. In the test that had been done by SPIN-BC and SPIN-RL routing with nodes of 4,8,12,16, and 20 had latency mean value of 0.01856 ms, while the SPIN-RL routing had an average value of 0.83633 ms. The average test of NB Packet Data Forward on SPIN-BC routing was obtained averaged of 1.605 ms and SPIN-RL was obtained average of 7.88917 ms. The average value that was obtained by TX Power on SPIN-BC and SPIN-RL routing testing was 0.63292 mw. Furthermore, the average result that was obtained from Nb Tx Frame parameter on SPIN-BC routing was 1.7 ms, while SPIN-RL was obtained average of 7.9 ms. Then the test of the average result from the memory node was on SPIN-BC 7,56 MB, and SPIN-RL 34,454 MB. Based on the average results above, it can be concluded that SPIN-RL had better performance compared with SPIN-BC, because SPIN-RL can cope with command transmission error that was caused by data loss.